THE DESCRIPTION OF THE CITY’S FROM THE PEN OF GREAT PILGRIM - Türkan POLATCI (Fırat University, 2019)
Evliya Çelebi is a great Turkish travveller who lived in 17th century and made an international fame thanks to the book he wrote,‘Seyahatname’. He gave really important political, social and cultural information about the 17th century’s Vienna at ‘Seyahatname’ that he wrote with the impression of Vienna journey which he went with Kara Mehmet Pasha. The large content of this ‘Seyahatname’ made this work extra significant and gave it an international value. The work consists lots of information about Ottoman and its neighbourhood that it’s not found in any other source. Evliya Çelebi was a traveller who told the facts not only with the palace’s but also the public’s perspecpective in contradistiction to the chroniclers of the period of his period. Evliya Çelebi could write all the facts out of the palace, furthermore he gave information in different issues just like what the sultans of his period laugh at or cry. In literary, Seyahatname is the first excellent sample in its kinds; in terms of method, content and presentation features. The language he used in his work was not artfully, it was an active language which was used by the public. In this study, we tried to tell the Vienna impression on Evliya Çelebi in 17th century. Evliya Çelebi used extremely exaggerated expressions about Vienna in accordance with the diplomatic structure of the period. He also told his experience of appearing before Ceaser in a sarcastic way. Despite the strong language in his depiction, when it needed he also wrote about the knowledge, intelligence and the good sovereignty of Ceaser. In this aspect, ‘Seyahatname’ contains highly objective observations unlike the most of European travellers of the preiod.